Optimizing Production of Extracellular Laccase from Grammothele Subargentea CLPS No. 436 Strain - Saparrat, Mario Carlos Nazareno (2004)
The production of extracellular laccase by the Grammothele subargentea CLPS no. 436 strain in liquid cultures grown on a carbon-limited basal medium was significantly enhanced when culture conditions, including the addition of CuSO4·5H2O or veratryl alcohol, were consecutively optimized. A laccase activity as high as 1954.5 mU ml−1 of liquid medium was obtained under optimum conditions, which corresponded to non-agitated cultures supplemented with 0.6 mM CuSO4·5H2O. Veratryl alcohol at 1 mM was less effective than CuSO4·5H2O for increasing laccase activity levels; the supplementation of veratryl alcohol resulted only in maximum levels of 44 mU ml−1 in non-agitated cultures.